Clonixinato de lisina no tratamento de diversas patologias - Quevedo, Adhemar Arce; Okamoto, Auro Mitsuo; Mesquita, Carlos Telles; De Araújo Filho, Celso Machado; Albuquerque, Elisa; De Oliveira, Hildoberto Carneiro; Titonelli, Iraci; Cação, João Castilho [UNESP]; Catcagnolo Filho, José; Ponte, José Fernando Souza; De Oliveira, José Fernando Souza; Fogaça, Luiz Antônio Nogueira; et al. (My University, 1997)
In order to determine both efficacy and safety of lysine clonixinate in the treatment of various pathologies (migraine, dysmenorrhea, lumbago, orthopedic traumas and toothaches), we have conducted an open, non comparative study on 236 patients. The analgesic effect was excellent, and same patients even showed the maximum analgesic effect after five minutes. The lysine clonixinate tolerability proved excellent in this study, and has already been described at length in many other reports.
Lysine clonixinate in the treatment of various pathologies
Keywords: Dysmenorrhea; Lumbago; Lysine clonixinate; Migraine; Orthopedic traumas; Toothaches